2020
DOI: 10.1186/s13705-020-00269-y
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to a sustainable development framework for bioenergy in Malaysia: policy suggestions to catalyse the utilisation of palm oil mill residues

Abstract: Background The global commitment to climate change mitigation enforces the worldwide development of renewable energy sources. Therefore, various studies have investigated the growth of renewable energy in Malaysia, most commonly based on biogas and hydropower. In this article, the dynamics of Malaysia’s renewable energy development is critically examined by using the latest official national reports and other reliable resources. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 53 publications
(67 reference statements)
0
24
0
Order By: Relevance
“…The solution to the above world scenarios can be performed in various ways, and oil palm residues can be used for a versatile energy generation. It is estimated that about 2400-7460 MW of potential installed capacity could be yielded from OPKS, OPEFB, and OPMF, whereas about 410-483 MW power could be produced from POME biogas with 7200hr/year of operating hours [69]. Of all the different types of processes available globally, only two main methods are well known for their complete usability to transform waste into energy (WtE), such as thermochemical processes (gasification, pyrolysis, and direct combustion) and biochemical processes (anaerobic digestion, aerobic digestion) to produce solid, liquid, and gaseous biofuels.…”
Section: Palm Oil and Its Residues For Sustainable Biofuel And Bioenergy Productionmentioning
confidence: 99%
“…The solution to the above world scenarios can be performed in various ways, and oil palm residues can be used for a versatile energy generation. It is estimated that about 2400-7460 MW of potential installed capacity could be yielded from OPKS, OPEFB, and OPMF, whereas about 410-483 MW power could be produced from POME biogas with 7200hr/year of operating hours [69]. Of all the different types of processes available globally, only two main methods are well known for their complete usability to transform waste into energy (WtE), such as thermochemical processes (gasification, pyrolysis, and direct combustion) and biochemical processes (anaerobic digestion, aerobic digestion) to produce solid, liquid, and gaseous biofuels.…”
Section: Palm Oil and Its Residues For Sustainable Biofuel And Bioenergy Productionmentioning
confidence: 99%
“…Indonesia topped the list in expanding the geothermal energy capacity by 306 MW and is soon approaching a 2 GW total geothermal capacity [23]. Similarly, Malaysia is the third-largest producer of photovoltaic cells in the world while solar is responsible for sourcing the majority (47% in 2017) of the grid-connected renewable power generation in Malaysia [24].…”
Section: Current Status Of Renewable Energy Deployment In the Aseanmentioning
confidence: 99%
“…The problem of energy access and equity has not only been faced by Indonesia but also other countries in Asia such as Malaysia. A comprehensive and inclusive bioenergy policy towards a sustainable future of renewable energy development also need in Malaysia (Salleh et al, 2020). Another study in South-East Asia shown that providing power from residual biomass in small agricultural communities would reduce environmental impacts significantly while improving waste management practices.…”
Section: Introductionmentioning
confidence: 99%